Destination Service Quality and Destination Image To Enhance Revisit Intention: Role of Perceive Risk in Post-Covid-19 Era - Lia Febria Lina; Berlintina Permatasari; Dian Novita; Angga Febrian (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: The tourism industry has made an important contribution to the economy and society in various countries, including Indonesia. Purpose: The purpose of this study is to examine Destination Service Quality (DSQ) on Destination image and the revisit intention of tourists. By exploring and understanding the specific aspects of service quality, this study provide better comprehend how these elements contribute to a tourist's overall satisfaction and their likelihood to revisit. Tourists' perceived risk is examined as a moderating variable.Design/methodology/approach: This study used Quantitative method. This study surveyed 295 local and international tourists who met the criteria. This research utilizes PLS-SEM 7.0, a flexible statistical method for hypothesis testing, ideal for complex models with multiple variables. Findings/Result: The results of this study prove that the dimensions of destination service quality: accommodation, hospitality, cleanliness, and airport service, positively influence the destination image. The destination image has a positive effect on revisit intention. Conclusion: The findings prove that destination image is a key factor in determining revisit intention. Despite the influence of various service quality dimensions, the overall perception of the destination strongly drives the revisit intention. The study shows that destination service quality, particularly accommodation, hospitality, cleanliness, and airport service, significantly shapes the positive image of Lampung, encouraging repeat visits. However, the perceived risk, such as health concerns like COVID-19, does not significantly moderate this relationship, indicating that these concerns do not deter tourist's revisit intention.Originality/value (state of the art): This study underscores the theoretical importance of destination image in tourism studies and highlights the practical necessity for destination managers to prioritize and enhance this image to encourage revisit and foster tourist loyalty. Keywords: destination service quality, destination image, indonesia tourism, revisit intention, perceived risk, tourist behaviour